(untitled) (Research, Society and Development, 2021)
Burnout Syndrome (BS) is a tripod of emotional exhaustion, depersonalization and lack of professional fulfillment, its cause and origin are multifactorial. In the university, the victims of this syndrome are usually the students, more specifically those of medicine, due to the tension of fulfilling the demands of the course. Thus, we sought to establish the problem of BS in medical students through the integrative review. The study was organized through research on scientific journal platforms, mapping the information. There is no defined main cause for the disorder, but the sum of multiple elements facilitates the onset of BS, whether extrinsic or intrinsic factors. It can start at the time of medical school, continues throughout the residency, and grows in the routine of active physicians. Finally, the medical student faces an extensive curriculum with an intense means of productivity, which generates physical and mental exhaustion during their training, in addition to charging the student to be and behave like a good professional.